Educators and Students - Rahmania, Fadilla; Khairana, Cindy; Zulmi, Yuriz; Krisnawati, Ike; Adriantoni, Adriantoni (Education Achievement: Journal of Science and Research, 2024)
This research aims to explore the dynamics between educators and students in the context of formal education, with a focus on the roles and interactions of both parties in the learning process. The methods used include direct observation in class, in-depth interviews with educators and students, as well as analysis of related documentation. The research results show that learning effectiveness is greatly influenced by the quality of the relationship between educators and students, where good communication and appropriate pedagogical approaches can increase student motivation and participation. Educators who are able to understand students' individual needs and apply inclusive and adaptive teaching methods tend to be more successful in creating a positive and productive learning environment. This research emphasizes the importance of professionalism and empathy in the role of educators as well as the active involvement of students in the educational process to achieve optimal learning outcomes. It is hoped that these findings can contribute to the development of more effective and humane educational strategies.